2021
DOI: 10.3390/rs13204188
|View full text |Cite
|
Sign up to set email alerts
|

Important Airborne Lidar Metrics of Canopy Structure for Estimating Snow Interception

Abstract: Forest canopies exert significant controls over the spatial distribution of snow cover. Canopy snow interception efficiency is controlled by intrinsic processes (e.g., canopy structure), extrinsic processes (e.g., meteorological conditions), and the interaction of intrinsic-extrinsic factors (i.e., air temperature and branch stiffness). In hydrological models, intrinsic processes governing snow interception are typically represented by two-dimensional metrics like the leaf area index (LAI). To improve snow int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…We observed a reduction of the overall accumulation rate between 28% and 36% for the forested, compared to the open clusters. This observation, dominated by the interception of snow in the canopy, corresponds in its magnitude to existing literature values (Moeser et al, 2015;Russell et al, 2021). The high correlations between individual accumulation events (R: 0.81 -0.83) also agree with findings by Mazzotti et al (2022).…”
Section: Clusters Of Snow Distribution In Forestssupporting
confidence: 89%
See 2 more Smart Citations
“…We observed a reduction of the overall accumulation rate between 28% and 36% for the forested, compared to the open clusters. This observation, dominated by the interception of snow in the canopy, corresponds in its magnitude to existing literature values (Moeser et al, 2015;Russell et al, 2021). The high correlations between individual accumulation events (R: 0.81 -0.83) also agree with findings by Mazzotti et al (2022).…”
Section: Clusters Of Snow Distribution In Forestssupporting
confidence: 89%
“…Assuming low wind speeds, spatial variability of snowfall (accumulation) events over forested areas are dominated by interception and subsequent sublimation processes of snow in the tree canopy. Its magnitude depends strongly on the three-dimensional (3D) structure of the canopy (Moeser et al, 2015;Russell et al, 2021). Interception reduces accumulation in coniferous forests by 30-40%, depending on vegetation characteristics and meteorological conditions (Broxton et al, 2014;Jost et al, 2007;Varhola et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, at the forest stand level (40 m wide) of our study, θ showed a good correlation relationship with all the snow sub-processes (interception, sublimation, and snowmelt). Similar to previous studies on the relationship between canopy closure (or LAI) and snow processes as determined using different scales and methods by Krogh et al (2020), Broxton et al (2021), andRussell et al (2021), we also found that θ was an ideal canopy index factor to explain the variations in SD, Ic, S s , S r , and SWE in the mixed forests of the Changbai Mountains.…”
Section: Influence Mechanism Of Forest Canopy Closure On the Snow Pro...supporting
confidence: 89%
“…A variety of forest structure indicators have been used to reveal the impact of forests on snow processes, such as forest cover (Varhola et al, 2010;Pomeroy et al, 2012;Varhola and Coops, 2013), canopy cover (Pomeroy et al, 2002), leaf area index (Gelfan et al, 2004;Woods et al, 2006;Rutter et al, 2009;Lendzioch et al, 2019), and canopy closure (Broxton et al, 2021). In the meantime, as technology continues to progress, various methods have been applied comprehensively, such as forest snow sampling survey (Watson et al, 2006;Parajuli et al, 2020), snow model simulation (Pomeroy et al, 2007;Rutter et al, 2009;Krinner et al, 2018;Napoly et al, 2020), statistical modeling (López-Moreno andNogués-Bravo, 2006), snow remote sensing (Zhang et al, 2010;Frei et al, 2012;Hojatimalekshah et al, 2021), LiDAR technology (Harpold et al, 2014;Broxton et al, 2021;Russell et al, 2021), UAV remote sensing (Lendzioch et al, 2019), and delayed photography (Parajka et al, 2012;Dong and Menzel, 2017). When studying forest snow process in specific areas, the most appropriate method needs to be selected and balanced, as each method has certain advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%